Síntese de acil fosfodiésteres por mecanoquímica: uma metodologia de química verde - Patrocinio, Katiana Lima do (Universidade Federal de São Carlos, 2019)
Green chemistry is very concerned with the sustainability of chemical reactions, where one of the objectives, which in the formulation/remodeling of synthetic routes can replace toxic solvents with solvents of lower toxicity, can be highlighted the methodologies that use none or a minimum of solvents. Mechanochemistry is a technique that employs the mechanical maceration of reagents without solvents, achieving excellent results in less reaction time. This technique can improve traditional reactions that have low yields of products with high value, such as acyl phosphates. Phosphate esters have a wide application such as enzymatic substrates, surfactants, and prodrugs, and their synthesis employs several steps with highly toxic reagents and solvents. Therefore, in this work, we aimed at the synthesis of acyl phosphates via mechanochemistry to improve the sustainability of these processes. The methodology was optimized and involved the use of acyl chloride and a phosphate source in the presence of tetrabutylammonium bromide, eliminating excess solvents and decreasing reaction time from hours to minutes. Tetrabutylammonium bromide was shown to be essential for the selectivity towards the phosphate diester, and its role in the reaction was evaluated by molecular dynamics simulations. From the simulations, it was evident that the size of the carbonic chain from the acyl chloride had a major influence in the reaction outcome, in which the tetrabutylammonium bromide was needed to order the acyl chloride in the solid matrix. Comparatively, despite its low yields (maximum 50%), the methodology of this work presented better values of the E-factor and environmental coefficient than the ones described in the literature, exhibiting great potential in the sustainable synthesis of acyl phosphates.
Synthesis of rent phosphodesters by mechanochemistry: a methodology of green chemistry
Keywords: Química verde; Acil fosfodiésteres; Mecanoquímica; CIENCIAS EXATAS E DA TERRA::QUIMICA